PERANAN AKAL DALAM MEMAHAMI ILMU PENGETAHUAN - Kaleb Lelo; Alisa Marta Boimau; Ivani Arnelia Loden; Jesi ottu; Jenilia Hoar Klau; Aksa Nesta Naitboho; Joymetri Chingli Lenama (ADIBA : JOURNAL OF EDUCATION, 2025)
This article discusses the essential role of reason in the acquisition, organization, and verification of knowledge, especially through the method of literature study. In the realm of science, reason functions not only as a thinking tool for processing information but also as an epistemological foundation that enables researchers to provide critical analysis and interpret various types of written sources. This research, which uses a literature review approach, examines how reason aids in analytical thinking and synthesis when identifying key ideas, comparing various theoretical perspectives, and organizing coherent arguments from existing literature. Furthermore, reason also plays a crucial role in assessing the credibility and validity of literary sources, as well as in making logical inferences to draw appropriate conclusions and develop new insights from written data. The ability of the mind to reflect and reconstruct existing knowledge is the main driver of progress in scientific discussions. Therefore, this writing emphasizes that reason is an essential and inseparable element for every scientific endeavor based on literature studies, ensuring objectivity, consistency, and advancement in the understanding of knowledge.